Enhancing High School English Teaching: Integrating EdPuzzle Media in Kurikulum Merdeka Modules - Sheila Agustina; Fika Megawati; Yuli Astutik; Masliha Alfiatul Aqliyah (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article aims to investigate the integration of EdPuzzle media in teaching modules developed by high school English teachers following the Kurikulum Merdeka (KM) framework. Using document analysis, 16 EdPuzzle-integrated teaching module documents were qualitatively examined to understand teachers' preferences in selecting materials, methods, models, and assessments. The findings reveal that teachers successfully developed modules aligned with learning objectives and KM characteristics, incorporating EdPuzzle as both teaching material and assessment method. The study indicates a preference for narrative text topics, blended-learning models, and discussion methods. Writing skills were predominantly assessed using short-answer techniques, with EdPuzzle media mainly utilized for learning material rather than assessment. The implications suggest the need for teachers to diversify learning approaches, explore innovative techniques, and integrate technology effectively for an enhanced English Language Teaching experience. Highlight: The study explores the integration of EdPuzzle media in teaching modules within the context of Kurikulum Merdeka. High school English teachers successfully adapt teaching modules to align with learning objectives and KM characteristics. The majority of teachers utilize EdPuzzle both as learning material and as an assessment method, particularly in the context of narrative text topics. Keyword: Kurikulum Merdeka, Teaching Modules, EdPuzzle Integration, High School English Teachers, Document Analysis.